Immediate effects of diacutaneous fibrolysis in athletes with hamstring shortening. A randomized within-participant clinical trial. - Aïda Cadellans-Arróniz; Carlos López-de-Celis; Jacobo Rodríguez-Sanz; Albert Pérez-Bellmunt; Noé Labata-Lezáun; Vanessa González-Rueda; Luis Llurda-Almuzara; Pere Ramón Rodríguez-Rubio (PLoS ONE, 2022)
Background Diacutaneous fibrolysis is a non-invasive instrumental physiotherapeutic technique, used to treat mechanical or inflammatory pain and normalize function in the musculoskeletal system. Different studies have reported positive effects on range of motion, strength or function in musculoskeletal disorders, mainly in the upper extremity. The incidence and recurrence rates of hamstring injuries are high in many sports. However, there are no studies assessing these parameters in the hamstring and gluteus maximus in athletes. Objective. To evaluate the immediate and 30 minutes post-treatment effects of a single diacutaneous fibrolysis session on hamstring length, flexibility, muscle strength, myoelectrical activity and lower limb performance in athletes with hamstring shortening. Methods A randomized within-participant clinical trial. Sixty-six athletes with hamstring shortening were recruited. A single session of diacutaneous fibrolysis was applied following the cetripetal protocol to the gluteus maximus, biceps femoris and semitendinosus of for the experimental lower limb, whereas the control limb was not treated. Hamstring length (Passive knee extension test), hamstring and low back flexibility (Modified back saver sit and reach test), hamstring and gluteus maximus strength and electrical activity (dynamometry and surface electromyography, respectively) and lower limb performance (Countermovement Jump) were tested before treatment (T0), after treatment (T1), and 30 minutes post-treatment (T2). Results We only found a statistically significant difference between T0-T2 for the hamstring length favouring the experimental limbs (p<0.001). There were no statistically significant changes for hamstring and lower back flexibility, strength and electrical activity outcomes between groups. In the countermovement jump, we found a decrease of 0.58 cm in the high jump and a decrease of 9.19 N in the power jump at T1. These values recovered and improved at T2. However, these changes were not statistically significant (p>0.05). Conclusions A single session of diacutaneous fibrolysis in athletes with hamstring shortening, following the centripetal protocol for the posterior part of the thigh, produces improvements in hamstring length 30 minutes after, and in gluteus maximus strength immediately and 30 minutes after the treatment. It seems to have no effects on the overall hamstring and lower back flexibility or myoelectric activity. Importantly, the lower limb performance was not impaired after the treatment.